Caracterização molecular de isolados clínicos de Sporothrix spp. oriundos de felinos domésticos do estado da Paraíba - Angelo, Debora Ferreira dos Santos (2021)
Sporotrichosis is a subcutaneous mycosis caused by dimorphic fungi of the genus Sporothrix. This disease can affect man and a wide variety of animal species, especially the domestic cat, which has a very important epidemiological role in maintaining this disease in the urban environment. Being considered an endemic disease in Brazil. In the state of Paraíba, the first cases in domestic animals are relatively recent, with little epidemiological information on the outbreaks in felines and humans. In view of this, this work aims to identify molecularly isolates of Sporothrix spp. isolated from domestic cats from cities in Paraíba, and in this way expand the understanding of the disease in the state. 39 samples of skin lesions were collected from domestic cats, from the following cities in Paraíba: João Pessoa (n = 29), Pilões (n = 4), Patos (n = 3), Areia (n = 1), Bananeiras (n = 1) and Guarabira (n = 1). The samples were initially processed at the Preventive Veterinary Medicine Laboratory of the Agricultural Sciences Center of the Federal University of Paraíba, Paraíba, Brazil, where the diagnosis at the gender level was established by means of fungal culture. Then, the samples were sent to the Mycology Laboratory of the National Institute of Infectology Evandro Chagas, Rio de Janeiro, Brazil, where the molecular characterization of fungal isolates was performed, using species-specific PCR for S. schenckii sensu stricto, S. brasiliensis and S. globosa or partial sequencing of the calmodulin gene. This study revealed that 100% of the isolates belonged to the species Sporothrix brasiliensis, and the sequence alignment and phylogenetic analyzes of six isolates showed 100% similarity to the S. brasiliensis strain CBS 120339. The evaluation of the significance of the phylogenetic tree, carried out by by means of the Bootstrap test, it revealed in this evaluation with 1,000 replicates, a 98% confidence level for the occurrence of nodes. With the molecular analysis described in this study, the occurrence of Sporothrix brasilienses was shown for the first time in cats from the Northeast region of Brazil. Reinforcing the role of this species of Sporothrix in feline sporotrichosis in the state. The identification of S. brasiliensis in felines from Paraíba highlights the occurrence of the predominant agent in large zoonotic outbreaks in the South and Southeast regions of Brazil in distant geographic areas, alerting to the possible occurrence of zoonotic outbreaks similar to those found in these regions, and highlights the role of the feline in the zoonotic transmission of sporotrichosis, considering that this genotype is observed in the disease in humans. Finally, these data support the adoption of preventive measures against animal disease, which will potentially impact the epidemic in the city of João Pessoa, as well as the alarming emergence of cases in the interior of the state.